CAREER CHOICE OF BUILDING ENGINEERING EDUCATION ALUMNI OF PALANGKA RAYA UNIVERSITY - Dendy Yuli Setiawan; Wiratno (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
Career choice is the determination of a career that affects a person's position, where the determination is influenced by several factors either internal factors or from the individual or external or from outside the individual for the sake of progress and survival. This research aims to find out: 1. what percentage of alumni career choices in the field of education, non-education but related to Building Technology and not both 2. whether alumni career options fit the profile of graduates 3. or the curriculum has significantly affected alumni careers. This research is a descriptive study with a quantitative approach, the subject of this study is an alumniof Building Engineering Education of Palangka Raya University in June 2021 with a population of 83 alumni and a sample number of 40 alumni. Questionnaires on the likert scale are used as instruments to collect the necessary data, these questionnaires are created in the form of google forms and distributed online to alumni. Then, the data is analyzed using the achievement degree formula (DP). The results showed that the highest percentage of consecutive career choices, not educators and not related to the field of building engineering science (62.5%), not educators but still related to the field of building engineering (22.5%) and educators (15%). And alumni students who choose a career according to the graduate profile of the Building Engineering Education study program curriculum by (37.5%) and the non-conforming (62.5%). So it can be concluded that most of the alumni of Building Engineering Education students in their career selection do not match the profile of graduates of the curriculum of the Building Engineering Education Study Program of Palangka Raya University. While the average percentage of the influence of the Building Engineering Education curriculum on alumni in a career is 73.18% and belongs to the category quite well. This shows that the curriculum of Building Engineering Education is significantly quite good in influencing alumni in a career